Association of Family Cancer History With Pathogenic Variants in Specific Breast Cancer Susceptibility Genes. (22nd December 2021) - Kurian, Allison W.; Abrahamse, Paul; Ward, Kevin C.; Hamilton, Ann S.; Deapen, Dennis; Berek, Jonathan S.; Hoang, Lily; Yussuf, Amal; Dolinsky, Jill; Brown, Krystal; Slavin, Thomas; Hofer, Timothy P.; et al.
Abstract : PURPOSE: Family cancer history is an important component of genetic testing guidelines that estimate which patients with breast cancer are most likely to carry a germline pathogenic variant (PV). However, we do not know whether more extensive family history is differentially associated with PVs in specific genes. METHODS: All women diagnosed with breast cancer in 2013-2017 and reported to statewide SEER registries of Georgia and California were linked to clinical genetic testing results and family history from two laboratories. Family history was defined as strong (suggestive of PVs in high-penetrance genes such as BRCA1/2 or TP53, including male breast, ovarian, pancreatic, sarcoma, or multiple female breast cancers), moderate (any other cancer history), or none. Among established breast cancer susceptibility genes ( ATM, BARD1, BRCA1, BRCA2, CDH1, CHEK2, NF1, PALB2, PTEN, RAD51C, RAD51D, and TP53 ), we evaluated PV prevalence according to family history extent and breast cancer subtype. We used a multivariable model to test for interaction between affected gene and family history extent for ATM, BRCA1/2, CHEK2, and PALB2 . RESULTS: A total of 34, 865 women linked to genetic results. Higher PV prevalence with increasing family history extent ( P < .001) was observed only with BRCA1 (3.04% with none, 3.22% with moderate, and 4.06% with strong history) and in triple-negative breast cancer with PALB2 (0.75% with none, 2.23% with moderate, and 2.63% with strong history). In a multivariable model adjusted for age and subtype, there was no interaction between family history extent and PV prevalence for any gene except PALB2 ( P = .037). CONCLUSION: Extent of family cancer history is not differentially associated with PVs across established breast cancer susceptibility genes and cannot be used to personalize genes selected for testing. Abstract :